Modelling and stability investigations of an aggregate wind farm–fed multi-machine system. Issue 6 (December 2020) - Ahsan, Hailiya; Mufti, Mairaj-ud-Din
This article presents a detailed mathematical modelling and integration of a substantial 300-MW wind farm in a New England 39-bus system for stability investigations. Machine modelling is achieved using the differential algebraic equations from the two-axis model, in the form of a flexible network function. An aggregated wind farm model is developed with the order of hundreds of wind turbines, driving an aggregate doubly fed induction machine feeding the multi-machine system. Stability studies are performed on the non-linear model in MATLAB-Simulink platform, with exogenous disturbances of a continuous disturbed wind and a three-phase short circuit with two different clearing times. Stability retention of the wind farm–fed system is affirmed with the extensive power balance, frequency supervision and profuse voltage levelling.